Black Mold on Tomato Fruits Caused by Alternaria alternata in Korea - Wan-Gyu Kim; Jae-Taek Ryu; Hyo-Won Choi (한국균학회지, 2020)
Black mold was frequently observed on tomatoes grown in a greenhouse in Suwon, Korea in July 2018. The incidence of the disease was 5.0-25.0% (average 12.3%) and 2.0-7.0% (average 3.7%) in the context of tomato and cherry tomato fruits, respectively. Sixteen single-spore isolates of Alternaria sp. were obtained from the diseased fruits and investigated for their morphological characteristics. Among the isolates, eight were used for sequencing analysis. All of the isolates were identified as Alternaria alternata based on their morphological and molecular characteristics. The pathogenicity of four isolates of A. alternata was investigated using three varieties each of tomato and cherry tomato via artificial inoculation. All of the isolates induced black mold symptoms on the inoculated tomato fruits. Notably, the symptoms were similar to those observed in the greenhouse. However, the pathogenicity tests revealed that different tomato varieties presented distinct patterns of susceptibility to the isolates. This is the first report of A. alternata causing black mold on tomato fruits in Korea.